Prevalence and predictors of food insecurity among people living with and without HIV in the African Cohort Study - Onyenakie, Cecilia C.; Nnakwe, Raphael U.; Dear, Nicole; Esber, Allahna; Bahemana, Emmanuel; Kibuuka, Hannah; Maswai, Jonah; Owuoth, John; Crowell, Trevor A.; Polyak, Christina S.; Ake, Julie A.; Iroezindu, Michael (Public Health Nutrition, 2022)
We determined the prevalence and identified predictors of food insecurity in four African countries. Design: Cross-sectional analyses at study enrolment. Setting: From January 2013 to March 2020, people living with HIV (PLWH) and without HIV were enrolled at twelve clinics in Kenya, Uganda, Tanzania and Nigeria. Participants: Participants reporting not having enough food to eat over the past 12 months or receiving <3 meals/d were defined as food insecure. Robust Poisson regression models were used to estimate unadjusted and adjusted prevalence ratios (aPR) and 95 % CI for predictors of food insecurity among all participants and separately among PLWH. Results: 1694/3496 participants (48·5 %) reported food insecurity at enrolment, with no difference by HIV status. Food insecurity was more common among older participants (50þ v. 18–24 years aPR 1·35, 95 % CI 1·15, 1·59). Having 2–5 (aPR 1·14, 95 % CI 1·01, 1·30) or >5 dependents (aPR 1·17, 95 % CI 1·02, 1·35), and residing in Kisumu West, Kenya (aPR 1·63, 95 % CI 1·42, 1·87) or Nigeria (aPR 1·20, 95 % CI 1·01, 1·41) was associated with food insecurity. Residing in Tanzania (aPR 0·65, 95 % CI 0·53, 0·80) and increasing education (secondary/above education v. none/ some primary education aPR 0·73, 95 % CI 0·66, 0·81) was protective against food insecurity. Antiretroviral therapy (ART)-experienced PLWH were more likely to be food secure irrespective of viral load. Conclusion: Food insecurity was highly prevalent in our cohort though not significantly associated with HIV. Policies aimed at promoting education, elderly care, ART access in PLWH and financial independence could potentially improve food security in Africa.
Keywords: Food insecurity; HIV; Antiretroviral therapy; Africa; Food supply; Nutrition policy